Pengembangan Green Halal Tourism dengan Metode Soar dan Analytical Hierarchy Process - Firman Setiawan (Jurnal Ilmiah Ekonomi Islam, 2023)
The concept of halal and green tourism is often a partial study of tourism development in Indonesia. When researchers and academics discuss halal tourism, generally, they will be separated from environmental issues. On the other hand, when environmental issues are raised in the tourism industry, the sharia aspects are ignored. This study examines the development of green halal tourism as a synthesis of the two tourism concepts. This research uses SOAR and AHP methods. The study was conducted at the Makam Agung Arosbaya tourist attraction, a tourist attraction that best represents this tourism genre. From the analysis carried out, it is known that there are several things, from strengths, opportunities, aspirations, and results, which can then be used as strategies and priority plans in the development of eco-halal tourism based on the SOAR analysis index and the AHP consistency value. This strategy and planning are classified into environmental, socio-cultural, facilities and services, promotion, historical tourism, and economic aspects. Priority plans that must be carried out in the development of eco-halal tourism include environmental conservation, maintenance of archaeological sites, prevention of negative cultural influences on local wisdom values, improvement of facilities and services for tourists, use of online media for promotion, introduction to the history of figures Makam Agung Arosbaya, as well as optimizing tourism objects as new markets for local products, both goods, and services.